1999
DOI: 10.1007/bf02462485
|View full text |Cite
|
Sign up to set email alerts
|

Visual evoked potentials in humans during recognition of emotional facial expressions

Abstract: Visual evoked potentials were recorded from the occipital, parietal, central, frontal, and posterior temporal areas of the cortex during recognition of emotionally positive, negative and neutral facial expressions and during passive observation in 22 right-handed healthy subjects. These studies showed that in the posterior temporal areas, the latencies of the N90, P150, and N180 waves of potentials evoked by faces with emotionally negative expressions were significantly shorter than those evoked by other types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…We surmise that the preserved ERP and behavioral effects might be linked, pointing to a processing stage at around 150–250 ms poststimulus onset mediating both explicit fear perception and emotional effects on working memory. This hypothesis accords with previous ERP data in healthy participants that tentatively linked fearful ERP effects at this time window to explicit processing of expression [Mikhailova and Davydov, 1999], and showed that these ERP responses to expressions depend on attention to the stimulus [Eimer and Holmes, 2007]. In any case, the preserved fear effect for this time-period in MTLE-amygdala subjects certainly demonstrates that not all processing of fearful faces depends on contributions from the amygdala, suggesting instead that there are multiple pathways for processing emotional information [Amaral, 2002; LeDoux, 1996; Vuilleumier, 2005], each involving differential neural structures and importantly operating with a specific time course.…”
Section: Discussionsupporting
confidence: 92%
“…We surmise that the preserved ERP and behavioral effects might be linked, pointing to a processing stage at around 150–250 ms poststimulus onset mediating both explicit fear perception and emotional effects on working memory. This hypothesis accords with previous ERP data in healthy participants that tentatively linked fearful ERP effects at this time window to explicit processing of expression [Mikhailova and Davydov, 1999], and showed that these ERP responses to expressions depend on attention to the stimulus [Eimer and Holmes, 2007]. In any case, the preserved fear effect for this time-period in MTLE-amygdala subjects certainly demonstrates that not all processing of fearful faces depends on contributions from the amygdala, suggesting instead that there are multiple pathways for processing emotional information [Amaral, 2002; LeDoux, 1996; Vuilleumier, 2005], each involving differential neural structures and importantly operating with a specific time course.…”
Section: Discussionsupporting
confidence: 92%
“…Similar reasoning could be applied to understanding why overall greater dot detection was positively correlated with emotional expressiveness, in that the listener's general state of attentional arousal could be affected by the talker's degree of facial emotional expressiveness. Interestingly, one view of the laterality of emotion perception-namely, that the right hemisphere is dominant in the perception of all emotions (Hellige, 1995;Mikhalilova, Davydov, & Morgunkova, 1996)-is 164 THOMPSON, MALMBERG, GOODELL, BORING consistent with our obtained correlation between dot detection performance on the talker's right side and emotional expressiveness. The correlation between clarity of pronunciation and dot detection in the left visual field is less easily explained.…”
Section: Discussionsupporting
confidence: 88%
“…The right hemisphere has been found to be the primary hemisphere active during emotion processing of faces (e.g., Gunning-Dixon, et al, 2003; Mikhailova, et al 1996), and for emotional prosody processing (e.g., Bryden & MacRae, 1989; Erhan, et al 1998; Grimshaw, 1998; Grimshaw, et al 2003; Stirling, et al 2000). We argue that, when emotional prosody is high, attention is biased to the region of the face that is contralateral to the right hemisphere, specifically, the left side of the face image.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies show a left visual field (right hemisphere) advantage for perceptual processing of static images of faces using tasks that do not involve language processing, but do involve emotion processing or making attractiveness judgments (e.g., Burt & Perrett, 1997; Klein, Moscovitch, & Vigna, 1976; Moscovitch, Scullion, & Christie, 1976). Topographic mapping of the brain shows that the right hemisphere activates when interpreting facial expressions of emotions (Gunning-Dixon, et al, 2003; Levy, Wagner, & Luh, 1990; Mikhailova, Davydov, & Morgunkova, 1996). Finally, Prodan, Orbelo, Testa, and Ross (2001) found that the right hemisphere was more highly activated when processing the upper region of the face while the left hemisphere was more highly activated while processing the lower region of the face.…”
Section: Lateralization Of Emotion and Language Processing: Behavioramentioning
confidence: 99%